1994
DOI: 10.1007/bf02066225
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and release of pheromone ofEpiphyas postvittana (Lepidoptera: Tortricidae) by apple leaves

Abstract: The absorption and release of the pheromone ofEpiphyas postvititana (Lepidoptera: Tortricidae),E 11-14: OAc andE,E 9, 11-14: OAc (95:5) by apple leaves was studied using electroantennograms (EAG) and sticky traps baited with pheromone-treated leaves. Leaves exposed to an airstream containing pheromone reached a constant level of pheromone release within 3 min. Release occurred over a period greater than 24 hr, following removal of leaves from the pheromone-saturated environment. Pheromone-treated leaves were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…The short Þeld lifetime of the formulation may explain, in part, the better performance of the mating disruption program in 2004, where there were four applications, compared with 2003, when only three applications were made. However, residual activity in the vineyard may have been slightly better because microcapsules in shaded areas, bark cracks, and other protected areas may have had a slightly longer effective lifetime (Karg et al 1994). The effective lifetime of microencapsulated materials is dependent on the microcapsule porosity and coating composition (Stipanovic et al 2004), which can be controlled, and ambient temperature, rainfall, and sunlight exposure (Bradley et al 1995, Millar 1995, Waldstein and Gut 2004, which cannot be controlled.…”
Section: Discussionmentioning
confidence: 99%
“…The short Þeld lifetime of the formulation may explain, in part, the better performance of the mating disruption program in 2004, where there were four applications, compared with 2003, when only three applications were made. However, residual activity in the vineyard may have been slightly better because microcapsules in shaded areas, bark cracks, and other protected areas may have had a slightly longer effective lifetime (Karg et al 1994). The effective lifetime of microencapsulated materials is dependent on the microcapsule porosity and coating composition (Stipanovic et al 2004), which can be controlled, and ambient temperature, rainfall, and sunlight exposure (Bradley et al 1995, Millar 1995, Waldstein and Gut 2004, which cannot be controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies revealed that insect-related volatiles including pheromones are adsorbed to various substrates, including glass (Colwell et al, 1978;Baker et al, 1980Baker et al, , 1981Pope et al, 1984;Yasui et al, 2003), filter paper (Phillips et al, 1996) and leaves (Noldus et al, 1991;Karg et al, 1994). 14:iBu and 18:iBu were detected in hexane solutions of rinses on the inner surface of glass beakers into which male R. clavatus were placed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, mating disruptant dispensers applied low in the canopy may not sufficiently mask a potentially competing female. In addition, absorption of codlemone onto orchard foliage varies by proximity to dispensers applied for mating disruption (Karg et al 1994) and gravid females may move to areas where concentrations are lower, such as the upper canopy or the edge of orchards. Thus, it may be important to treat orchard borders with more dispensers (Charmillot 1990) than the interior.…”
Section: Discussionmentioning
confidence: 99%